The Relationship Between Muscle Strength and Cognitive Performance Across Alzheimer's Disease Clinical Continuum - Filardi, Marco; Barone, Roberta; Bramato, Giulia; Nigro, Salvatore; Tafuri, Benedetta; Frisullo, Maria Elisa; Zecca, Chiara; Tortelli, Rosanna; Logroscino, Giancarlo (Frontiers in Neurology, 2022)
Alzheimer's disease (AD) is a neurodegenerative disorder characterized by a progressive cognitive decline, mostly prominent in the domain of memory, but also associated with other cognitive deficits and non-cognitive symptoms. Reduced muscle strength is common in AD. However, the current understanding of its relationship with cognitive decline is limited. This study investigates the relationship between muscle strength and cognition in AD and mild cognitive impairment (MCI) patients. We enrolled 148 consecutive subjects, including 74 probable AD dementia patients, 37 MCI and 37 controls. Participants underwent neuropsychological evaluation focused on attention, working memory, declarative memory and learning. Muscle strength and muscle mass were measured through hand dynamometer and bio-electrical impedance analysis, respectively. AD dementia patients were divided with respect to the severity of cognitive impairment into mild and moderate-to-severe patients. Moderate-to-severe AD patients presented lower handgrip strength than MCI and controls. No differences were observed in muscle mass. In MCI and AD dementia, handgrip strength was associated with overall cognitive functioning, and attentional and memory performance. The routine implementation of handgrip strength assessment in the clinical work-up of MCI and AD patients could potentially represent a simple method to monitor functional and cognitive decline along the disease course.